2010
DOI: 10.1039/c0ob00308e
|View full text |Cite
|
Sign up to set email alerts
|

Aminocyclopropanes as precursors of endoperoxides with antimalarial activity

Abstract: This contribution describes the synthesis of several novel bicyclic α-amino endoperoxides, including CF(3)-substituted compounds, prepared by the aerobic electrochemical oxidation of a family of bicyclic aminocyclopropanes. These, in turn, are readily synthesised by a titanium-mediated intramolecular cyclopropanation process (Kulinkovich-de Meijere reaction), starting from N-alkenyl amides that contain a vic-disubstituted double bond, with high diastereoselectivity. An evaluation of the biological activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…It is noteworthy that some of them exhibit moderate but significant in vitro activity against Plasmodium falciparum, the parasite responsible for malaria (Scheme 28). 116,117 Scheme 28. Electrosynthesis of moderately active antimalarial α-aminoendoperoxides.…”
Section: Formal [3+2] Cyclisation With Alkenes and Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that some of them exhibit moderate but significant in vitro activity against Plasmodium falciparum, the parasite responsible for malaria (Scheme 28). 116,117 Scheme 28. Electrosynthesis of moderately active antimalarial α-aminoendoperoxides.…”
Section: Formal [3+2] Cyclisation With Alkenes and Alkynesmentioning
confidence: 99%
“…These values range from about 0.5 V to +1.35 V vs saturated calomel electrode (SCE), depending on the substitution pattern, with the lowest potentials corresponding to aminocyclopropanes fitted with an electron-rich aromatic ring at the nitrogen atom. 114,115,116,117 The preparative aerobic anodic oxidation reactions of the aminocyclopropanes can then be conducted selectively and monitored by cyclic voltammetry:…”
Section: Formal [3+2] Cyclisation With Alkenes and Alkynesmentioning
confidence: 99%
“…The Buriez group showed that electrochemical aerobic oxidation of aminocyclopropane 40 underwent cyclopropane ring opening to furnish a distonic radical cation ( 42 ). This adduct readily reacts with molecular oxygen to ultimately afford α‐amino endoperoxide 43 (Scheme ), which were demonstrated to exhibit antimalarial activity . The Shono oxidation has also been utilized for the synthesis of an array of alkaloid skeletons, such as the intermolecular oxidative coupling of corypalline and intramolecular coupling of laudanosine …”
Section: Anodic Oxidationmentioning
confidence: 99%
“…This procedure is fast, convenient and flexible: the potential applied is adjusted to the optimal value for each substrate, which ensures good yields and selectivity (Scheme ) 4. 7…”
Section: Introductionmentioning
confidence: 99%
“… Synthesis of bicyclic α‐aminoendoperoxides by electrochemical aerobic oxidation of 2‐azabicyclo[3.1.0]hexane derivatives 4. 7 …”
Section: Introductionmentioning
confidence: 99%